The costs of instruction in Dominican School Dagupan City - Gamotin, Ma. Fe (Animo Repository, 1978)
This study attempts to find out how much did it cost Dominican School to educate the students who enrolled for the school year 1978-1979. Data were gathered through a critical analysis of the school documents for the school year 1978-1979 such as the following: statement of income and expenses, class programs which indicated the number of students every class and the daily schedule, schedule of salaries and payroll and teachers program which showed the load and the schedule of each faculty member. Two units of measure were used, namely: weekly student contact hours and total number of students enrolled as basis for computing the cost for each student.